Noah's gold - Cottrell Boyce, Frank 1959- (Macmillan Children's Books, 2021)
"You may be the smallest, but it doesn't stop you having the biggest ideas. Eleven-year old Noah sneaks along on his big sister's geography field trip. Everything goes wrong! Six kids are marooned on an uninhabited island. Their teacher has vanished. They're hungry. Their phones don't work and Noah has broken the internet. There's no way of contacting home . . . Disaster! Until Noah discovers a treasure map and the gang goes in search of gold"--Publisher's description
Keywords: School field trips / Juvenile fiction; Treasure troves / Juvenile fiction; Adventure stories; Children's stories; Juvenile works; Action and adventure fiction; Humorous fiction; Kinderbuch